Visualisasi Krisis Sosial dalam Tagar #PeringatanDarurat pada Media Sosial Instagram - Purnamasari, Widiyani Kuspi; Kurniawan, Khaerudin; Kusumah, Encep (Universitas Prof. Dr. Moestopo (Beragama), 2025)
A policy comes into existence that does not have a strong basis in the formation process and can trigger controversy and debate among the public. Social media, with its hashtag feature, has become a platform for people from all walks of life to voice their opinions. This research aims to reveal the meaning contained in Instagram posts with the hashtag #EmergencyAlert. The method used in this research is descriptive qualitative which refers to the theory of social semiotics proposed by Theo van Leeruwen. This research analyzes four main elements of social semiotics, namely discourse, genre, style, and modality. Data collection in this study was done by collecting and documenting Instagram content, then categorizing the content based on the #EmergencyAlert hashtag according to the number of interactions received. The results of this research were then developed into new semiotic resources to enrich future studies. The findings of this analysis show that posters shared on Instagram with the hashtag #EmergencyAlert have deep signification related to maintaining the integrity of democracy in Indonesia. The violation of people's sovereignty is understood as a protest action marked by the Blue Garuda Emergency Alert to the Government, which is shown by posting a poster in blue with the symbol of the garuda bird, accompanied by a call to the public to participate and monitor the government.